Pathological and Ultrastructural Findings of Sphaerospora dicentrarchi (Myxosporea: Bivalvulida) infection in European seabass (Dicentrarchus labrax) farmed in Turkey - Birincioğlu, SS; Avcı, H; Ipek, E; Berke, E; Birincioğlu, B; Aydogan, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Sphaerospora dicentrarchi is typically histozoic parasite of the wild and cultured European sea bass (Dicentrachus labrax) of the Mediterranean coastal countries. In this study, pathological and ultrastructural findings of the Sphaerospora dicentrarchi infection in European sea bass were firstly investigated in Turkey. For this purpose, the 862 European seabass (Dicentrarchus labrax L) were collected and evaluated from eight cultivation fish farms (offshore floating cages) in four different locations of Aegean Sea of Turkey (three farms from Kazıklı, one farm from Çandarlı, two farms from Taşburun and two farms from Güllük Regions). It was observed that the parasite was especially intense in adult fish and in the June-October period when the water temperature increased. Microscopically, the parasites were seen as the most intensive in the stomach, intestines, gall bladder, pancreas, heart and testis, respectively. Stomach was the most commonly infected organ. In the transmission electron microscopy examination, a bag-like group of mature couple spores were seen surrounded by polar capsules. As a result, it was determined that Sphaerospora dicentrarchi infection is very common in adult sea bass in the Aegean region of Turkey, as in Greece, Spain, Portugal and Italy.